Specialists or All-Rounders: How Best to Select University Students? - Pedro Luís Silva (Institute of Labor Economics (IZA), 2022)
This paper studies whether universities should select their students only using specialised subject-specific tests or based on a broader set of skills and knowledge. I show that even if broader skills are not improving graduates' outcomes in the labour market, the university chooses to use them as a criterion for selection alongside the mastery of more subject-specific tools. Empirically, I exploit the variation between subject-specific and non-specific entrance exam sets on Portuguese students' large administrative dataset. My central finding is that, on average, universities with less specialised admission policies admit a pool of students who obtain a higher final GPA.
Keywords: I23; I24; I28; J24; 330; university choice; admission tests; job market; general skills